Factors Affecting Innovative Work Behavior and Health Worker Performance: The Role of Employee Engagement as a Moderating Variable - Ria Emilia Sari; M. Arief (Journal of International Conference Proceedings, 2021)
This study aims to determine the factors that influence work behavior and health worker performance moderated by the role of employee engagement. This research aiming to explain the relationship among variables. This study involves 100 ABC hospital employees. The data obtained by survey method through the G-Form and analyzed use Smart PLS application. Based on the results of the study, it was found that (1) there is a significant positive effect between employee digital capabilities on employee performances, (2) there is a significant positive effect between employee digital capabilities on innovation work behavior, (3) there is a significant positive effect of employee engagement on employee performances, (4) there is a significant negative effect of innovation work behavior on employee performances, (5) there is a significant positive effect of performance management system on employee performance, (6) there is a significant positive effect of performance management system on innovation work behavior, (7) there is a significant positive effect of work motivation on employee performance, (9) there is a significant positive effect of work motivation on innovation work behavior, (10) H9, H10, and H11 are accepted where innovation work behavior is able to moderate the relationship of performance management system, employee digital capabilities, and work motivation on employee performance.